Varlam Cherkhezishvili against Marxism: Discussion with Karl Kautsky - Cherkezishvili, Varlam (Politics / პოლიტიკა, 2020)
The work of a famous Georgian anarchist, Varlam Cherkhezishvili – “You Have Avowed Finally” (The Answer to Karl Kautsky) was published in the Russian language in 1907, in Tbilisi. This was an answer to the article of Karl Kautsky, which tried to justify that the “Communist Party Manifesto” was not the plagiarism. This article of Karl Kautsky was considered as the plagiarism by Varlam Cherkhezishvili. The Georgian translations of the abovementioned works of Kautsky and Cherkhezishvili are published in the following journal.